The The Effectiveness Of The Pedestrian Path And Ramp On Jl. Imam Bonjol Corridor Semarang - Hetyorini Hetyorini Hetyorini; Susmita Eka Mukti; Aziz Maulana Maulana (Architecture Study Program, Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Semarang, Indonesia, 2023)
Pedestrian paths and ramps are public facilities that are used by pedestrians and people with disabilities in accessing a place, moving from one place to another, connecting to a destination or carrying out other activities in urban space. Provision of pedestrian paths and ramps must be accessible, effective, and keep activities in urban spaces running well. One of the pedestrian and ramp lanes in Jl. Imam Bonjol corridor Semarang is interesting to study in which the existence of pedestrian paths and ramps can be said is still limited to providing public facilities without regard to quality, continuity of function of facilities and respect for users, both pedestrians and people with disabilities. However, the condition of the pedestrian paths and ramps in Jl. Imam Bonjol corridor is good enough, but there are some significant things that can hinder the user's circulation. Several sections of pedestrian paths and ramps are used as parking lots for vehicles, rickshaws and cars. The guiding line for the blind is cut off in several places and sometimes even leads to an open exhaust channel. In some sections it turns out to be difficult for the disabled to use it. This fact is very unfortunate because pedestrians and people with disabilities have the same rights in the use of pedestrian paths and ramps. This study aims to provide design solutions to the problem of designing pedestrian paths and ramps on Imam Bonjol Semarang street corridor to connect urban activity centers so as to provide an ease and convenience access and improve the quality of urban space. A qualitative descriptive method is used in this research, namely by describing the problem to be studied in more depth in order to find solutions and develop the findings of previous studies.